Yang Tercampak dari Lebak: Refleksi atas Inspirasi Max Havelaar - Nanang Tahqiq (Budapest International Research and Critics University, 2019)
Max Havelaar: Or the Coffee Auctions of the Dutch Trading Company (Dutch: Max Havelaar, of de koffi-veilingen der Nederlandsche Handel- Maatschappy) is an 1860 novel by Multatuli (the pen name of Eduard Douwes Dekker), which played a key role in shaping and modifying Dutch colonial policy in the Dutch East Indies in the nineteenth and early twentieth century. In the novel, the protagonist, Max Havelaar, tries to battle against a corrupt government system in Java, which was then a Dutch colony.